The carbapenem-resistant Enterobacteriaceae threat is growing: NDM-1 epidemic at a training hospital in Turkey. Issue 1 (December 2016) - Karabay, Oguz; Altindis, Mustafa; Koroglu, Mehmet; Karatuna, Onur; Aydemir, Özlem; Erdem, Ali
Abstract Background Recently, new carbapenemases in Enterobacteriaceae strains and non-fermentative gram-negative bacilli have been reported. The New Delhi metallo‐β‐lactamase-1 (NDM-1) is a major problem around the world. The purpose of this article is to address the NDM-1Klebsiella pneumoniae epidemic detected in eight cases in our hospital. Methods Bacteria identified in this epidemic were from patients already admitted to the intensive care unit of the Sakarya University Training and Research Hospital during efforts toward establishment of infection surveillance and control program. Antimicrobial susceptibility testing of strains was performed using the VITEK 2 system (bioMérieux, France), E-test gradient strips (bioMérieux, France), and the disc diffusion test. For the metallo-beta-lactamase activity, the combined disc diffusion test and modified Hodge test as phenotypic tests were performed. To identify the resistance gene, the Xpert Carba-R kit (Cepheid Inc., USA) and an in-house multiplex polymerase chain reaction (PCR) method designed for five common carbapenemase genes (IMP, VIM, KPC, NDM-1, and OXA-48) were employed. The clonal relationship of these strains was explored by the repetitive PCR (rep-PCR, DiversiLab System, bioMérieux, France) method. Results During the December 2014 to March 2015 period, NDM-1 positiveK. pneumoniae strains were detected in eight patients. All of these strains were found to produce NDM-1, while two of them also revealed the presence of OXA‐48. The rep-PCR results reveal a clonal proximity of 95 % for six of the eight strains. Conclusions Our findings suggest the tendency of NDM-1-producing strains to spread in our country as well. A carbapenem-resistantK. pneumoniae threat may pose a great risk to our country. It is clear that more comprehensive infection control precautions should be implemented in our hospitals.